Literature Review Analysis of the Side Effects of Chemotherapy in Cervical Cancer Patients in Southeast Asia - Stephen Yustianto Pribadi; Fitriana Yuliastuti; Widarika Santi Hapsari (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Cervical cancer is a cancer that occurs in the cervical part of the uterus that is the area in the female reproductive organs which is the entrance to the uterus located between the uterus and the burrow of intercourse. Cervical cancer treatment is known to be in several ways, one of which is by chemotherapy. Chemotherapy is a treatment using drugs both oral and intravenous that aim to inhibit or kill cancer cells, but treatment with chemotherapy has many side effects for people with cervical cancer. This study aims to analyze the side effects of chemotherapy in cervical cancer patients in Southeast Asia using the literature review method. The references used are literature obtained from Google Scholar and Pub Med from 2014 to 2020. After reviewing 15 journals it was stated that the side effects of chemotherapy on cervical cancer patients in Southeast Asia were nausea and vomiting (34.28%), anemia (14.28%), neurotoxins (14.28%), alopecia (11.42%), allergic reactions (8.57%), thrombocytopenia (8.57%), leukopenia (5.71%) and stomatitis (2.85%).